Wearable sensor networks: A measurement study. (23rd July 2020) - Bujari, Armir; Gaggi, Ombretta; Palazzi, Claudio E.; Quadrio, Giacomo
Abstract: Wearable technology is no longer science fiction. Thanks to the growing capability in the production chain to miniaturize complex electronics, a wide variety of gadgets that can be worn or included in dresses and accessories have emerged. These smart gadgets can collect data about the physical condition of the user and/or the environment providing the basis for innovative and valuable services. The main goal of this paper is to assess this context through field experiments undertaken in a testbed comprised of sensing hardware deployed on open source boards such as Arduino. Moreover, coupled with the sensing tier, we propose a proof‐of‐concept deployment architecture enabling a wide range of wearable sensors to collect and transmit data to a logically centralized unit.